SOCIAL AWARENESS (Discourse Analysis of Novel Dalang Galau by Sujiwo Tejo) - Hamzah, Adi Ari (QAULAN: Journal of Islamic Communication, 2020)
Abstract: Sujiwo Tejo is an Indonesian novel writer who is considered a writer as well as a contemporary humanist. The themes in his novels always raise social, political or religious issues. The novel "Dalang Galau Ngetwit" is one of his works that raises social themes and brotherhood among religious communities, because these issues are realized increasingly fading with a variety of things that lie behind them. In the novel "Dalang Galau Ngetwit" Sujiwo Tedjo tries to give an understanding to the community about the importance of kinship without seeing what religion it adopts, helping one another and always living in harmony. In this novel's work, the writer sees social injustice in the text of Sujiwo Tejo's novel. To assess the work of the novel, the writer uses Teun A Van Dijk's Discourse Analysis which divides the discourse into three levels: macro structure, Superstructure and Microstructure. The problem formulated in this paper is, what is the meaning of the message conveyed by Sujiwo Tedjo through the novel "Dalang Galau Ngetwit" in seeing the social conditions of the community to religious harmony and how this novel is able to describe the attitude of the community in national and state activities towards the problem of changes that exist in the cultural conditions in Indonesia.